Anglo-French Relations 1898 - 1998
XIII, 211 p.
Keywords: From the Fashoda incident in 1898 to the current Blair-Jospin 'entente', this book reviews one century of Franco-British relations. Friend or foe? Partner or rival? Model or counter-model? The two countries continually wavered between two extremes. Yet, as this collection of papers show, they have always had more things in common than suspected in the first place, and there has always been a strong case for cooperation.